Maternal Lineage and Habitat Use Patterns Explain Variation in the Fecundity of a Critically Endangered Baleen Whale - Bishop, Ana L.; Crowe, Leah M.; Hamilton, Philip K.; Meyer-Gutbrod, Erin L. (Frontiers in Marine Science, 2022)
The critically endangered North Atlantic right whale population (Eubalaena glacialis) has experienced multiple periods of decreased reproduction within its observable history, which have played a role in the overall decline of the species. In addition to this synchronized variation in reproduction across the population, there exists considerable individual variation in fecundity. To determine the impacts of family history and habitat use behavior on these individual variations in fecundity, photo identification data collected during four decades of visual monitoring were used to create a calving index for sexually mature females that could be used to evaluate matrilineal influence on fecundity. Reproductive life histories were analyzed to assess fecundity variation within matrilines over time. Individual variations in fecundity were also assessed with respect to a recent climate-driven habitat distribution shift by a loyal cohort of right whales that use the Gulf of St. Lawrence during the summer and autumn seasons. Lifetime fecundity in the oldest known living reproductive female, or matriarch, in a matriline was positively associated with the fecundity of her female progeny. Sexually mature females that have used the Gulf of St. Lawrence since 2015 were significantly more likely to give birth over this time period compared to individuals who did not use that habitat. Individuals of both sexes were significantly more likely to use the Gulf of St. Lawrence if their mothers did as well; however, this association declined as offspring aged. These results provide insight on the environmental, behavioral, and genetic factors that contribute to individual variation in fecundity. Low calving rates and increased dangers posed by habitat use shifts in the past decade have played a major role in the species’ decline, and these new insights into the mechanistic drivers of right whale reproduction and habitat use show that lineage guides progeny behavior and reproductive success. As anthropogenic climate change continues to disrupt right whale seasonal distributions through changing ocean circulation patterns, understanding the demographic consequences of novel habitat use patterns will be essential to updating protective policies.